1995
DOI: 10.1128/cmr.8.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Hyperimmune globulins in prevention and treatment of respiratory syncytial virus infections

Abstract: Respiratory syncytial virus (RSV) is an important community and nosocomial respiratory pathogen for infants and young children. RSV causes especially severe disease in the prematurely born or those with chronic cardiopulmonary diseases. Elderly persons and those with T-cell deficiencies, such as bone marrow transplant recipients, are also at high risk for serious lower respiratory tract infections. To date, prevention of RSV infections by vaccination has proven elusive and no preventive drugs exist. Studies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(34 citation statements)
references
References 139 publications
(118 reference statements)
0
33
0
1
Order By: Relevance
“…Passively transferred antibodies can confer protection from RSV disease both in humans [35] and in murine models of maternal immunization with BBG2Na [19]. However, the protection conferred by maternal antibodies is transient, and prolonged protection requires associated infant immunization.…”
Section: Discussionmentioning
confidence: 99%
“…Passively transferred antibodies can confer protection from RSV disease both in humans [35] and in murine models of maternal immunization with BBG2Na [19]. However, the protection conferred by maternal antibodies is transient, and prolonged protection requires associated infant immunization.…”
Section: Discussionmentioning
confidence: 99%
“…In the search for alternatives, hyperimmune globulins with higher neutralising antibody titre against RSV (RSVIG) were developed. It proved that RSVIG indeed could provide better neutralising antibody titres [22,28]. In a randomised prevention trial, monthly administered high dose intravenous RSVIG proved to be bene®cial in terms of rate of hospitalisation, duration of hospitalisation and duration on the intensive care unit in children at high risk for severe RSV infection [21].…”
Section: Immunoglobulinsmentioning
confidence: 97%
“…It was suggested that with standard IVIG used in these studies insucient neutralising antibody titres were achieved. This was also the case in several other lots of standard IVIG tested [28]. In the search for alternatives, hyperimmune globulins with higher neutralising antibody titre against RSV (RSVIG) were developed.…”
Section: Immunoglobulinsmentioning
confidence: 98%
See 1 more Smart Citation
“…SCT recipients are at high risk of infectious complications during the immediate posttransplantation period. RSV infections during this time spread from the upper to the lower respiratory tract in 60% of cases, with an associated 60%-80% mortality [2].Studies in cotton rats and in infants have shown that IgG with a high titer of neutralizing antibody to RSV decreases the incidence of RSV spread from the upper to the lower respiratory tract [3][4][5]. Studies in infants have shown that monthly infusions of immune globulin (750 mg/kg) with high neutralizing antibody titers decreases the incidence of hospitalization for RSV lower-respiratory-tract infection in premature infants !6 months of age and in children !24 months of age with bronchopulmonary dysplasia, compared with untreated control subjects [6].…”
mentioning
confidence: 98%